Techno-Cultural Characterization of the MIS 5 (c. 105 – 90 Ka) Lithic Industries at Blombos Cave, Southern Cape, South Africa - Douze, Katja; Wurz, Sarah; Henshilwood, Christopher Stuart (PLOS ONE, 2015)
Blombos Cave is well known as an important site for understanding the evolution of symbolically mediated behaviours among Homo sapiens during the Middle Stone Age, and during the Still Bay in particular. The lower part of the archaeological sequence (M3 phase) contains 12 layers dating to MIS 5 with ages ranging from 105 to 90 ka ago (MIS 5c to 5b) that provide new perspectives on the technological behaviour of these early humans. The new data obtained from our extensive technological analysis of the lithic material enriches our currently limited knowledge of this time period in the Cape region. By comparing our results with previously described lithic assemblages from sites south of the Orange River, we draw new insights on the extent of the techno-cultural ties between these sites and the M3 phase at Blombos Cave and highlight the importance of this phase within the Middle Stone Age cultural stratigraphy.